ECOTOURISM DEVELOPMENT GUIDELINES IN OUDOMXAY PROVINCE, LAO PEOPLE’S DEMOCRATIC REPUBLIC - Vongsamoraphoum, Phennapha; Smith, Natnaree (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
The objectives of this research are (1) to survey the readiness and feasibility of ecotourism destinations in Oudomxay Province to accommodate tourists, (2) to analyze the environment for ecotourism, (3) to study the impacts of ecotourism on local communities and the environment, and (4) to suggest guidelines for the development of ecotourism in Oudomxay Province, Lao People’s Democratic Republic. The research engaged 26 key informants, comprising 15 government officials, 7 private sector stakeholders, and 4 tourists. Data were collected through a triangulation of methods: destination observation, in-depth semi-structured interviews with key stakeholders, and collaborative participatory workshops, and analyzed through content analysis. The findings reveal a significant paradox: (1) While Oudomxay’s destinations possess high potential underpinned by rich natural resources and foundational infrastructure, this is severely constrained by limited accessibility, underdeveloped promotion, and nascent conservation measures struggling to keep pace with tourism growth,2) Tourism has the potential for sustainable growth if it receives continuous support through resource management and community participation to maintain a balance between tourism and nature conservation, 3) Ecotourism has political support. In term of economic, it generates income but the cost of living is high. In term of social, local identities are maintained, yet overcrowding and safety are emerging issues. While technological digital platforms aid promotion, misinformation poses a considerable risk to the province’s reputation and (4) Ecotourism in Oudomxay Province faces problems of depleted resources and unsystematic management. The study concludes that tourism development should receive cooperation from all relevant sectors.